AXIOLOGY PROBLEMS OF THE CULTURE AND EDUCATION OF YOUTH NOWADAYS - Valentina I. Revyakina (Russian State Vocational Pedagogical University, 2015)
The aim of the investigation is to justify the priorities of culture and education as a guarantor of moral improvement of the Russian society at the beginning of the XXI century.Methods. Despite the socio-cultural lack of stability of the Russian social medium, quite mature qualities of the youth's civic consciousness, activity and volunteering for the good of society have been revealed on the basis of the methods of analyzing scientific and publicistic researches, surveys and questionnaire.Results and scientific novelty. The article deals with the problems that generated low level of culture and education amongst teenagers and youth under conditions of modern political regime and lack of former ideological guidelines. Destabilizing factors of the teenagers and students' motivation decrease towards perception and acquiring cultural-educational ideals are noted. The destructive role of the mass media including television and radio encouraging moral deformation of the coming generation and its intellectual immiseration is shown.It's underlined that undergraduates and students' subjective position as a basic index of cultural-educational competence development is expressed in the volunteering movement. The motives of volunteering movement are as follows initiation, independence of goal-setting and planning, self-realization aspiration, ability to put ideas into practice without external pressure. The meaning of education is characterized as reproduction and enriching of people's life values and ideals providing times connection and continuity of generations. The author's own thoughts about the role of education in the life of a modern person are accompanied by the analysis of students' attitudes and judgments on the matter.Practical significance. The research findings appeal to specialist audiences involved in the sphere of education.